Folic acid and birth defects: knowledge of the portuguese population (Portuguese Journal of Family Medicine and General Practice, 2006)
Objective: To evaluate the populations knowledge with regard to folic acid and its preventive role on congenital abnormalities. Methodology: The cross-sectional study was based on a telephone survey among individuals with 18 years or over, living in a household in Continental Portugal. The initial random sample consisted on 1211 households. Descriptive statistics and cross-tabular analysis were used to describe the results. Logistic regression analysis and Chi-square tests were applied in order to establish possible associations between populations knowledge on folic acid and independent variables (sex, age, education level). Results: Out of the 975 valid inquires, 48,5% of the respondents had heard about folic acid. The majority of the inquired women heard about this compound (51,4%) and among them 25-44 years old women presented the higher percentage of positive answers. Concerning education level, 82,8% of the high graduated individuals had heard about folic acid. Logistic regression analysis showed that sex (ORMasc./Fem.=1,59), education level (ORbasic education/high degree= 6,57) and age (OR³45 years/18-44 years= 1,47) were associated with the respondents knowledge on folic acid. From those who heard about folate, 11,0% indicated that folic acid prevented congenital abnormalities and 22,9% knew that pregnant women or women in childbearing age should have the supplementation. Only 15,4% of the respondents indicated the correct period to initiate the supplementation, i.e., before pregnancy. Conclusions: The main results indicated that about half of the sample never heard of folic acid, especially men and less educated persons. Also, a very important lack of knowledge of the correct period to start preventive supplementation was detected.
Keywords: Folic acid; Congenital anomalies; Knowledge